The importance of tourist guides in promoting the archaeological heritage of Copán, Honduras - Reyes Corea, Silvia Margarita (2025)
Cultural heritage promotes professional development, identity, and the national economy through tourism. The goal is to analyze the construction of habitus among tour guides working at the Copán Ruinas Archaeological Park, located in western Honduras. Concepts developed in field theory, frequently used in studies on tourism in Latin America, were considered. The literature review found no studies on habitus applied to cultural disseminators. French sociologist Louis Pinto describes it in four dimensions: dispositional, distributive, categorical, and economic. At the methodological level, semi-structured interviews were conducted with eight members of the Association of Tour Guides and two experts. Participant observation was also conducted during two days of fieldwork, supplemented by a review of secondary sources. Our contribution was to identify social practice in each of the dimensions. The guides value the passion for recognizing Mayan culture, have established strong ties with experts, and are committed to investing time and money in their training. However, they struggle to reflect on the ontology of their work.